Studying the Process of the Internal Combustion Engine Exhaust Gas Purification by an Electric Pulse - Kadyrov, Adil; Kryuchkov, Yevgeniy; Sinelnikov, Kirill; Ganyukov, Alexandr; Sakhapov, Rustem; Kukesheva, Aliya (Communications - Scientific Letters of the University of Zilina, 2022)
The article deals with method of purifying the exhaust gases in an automobile muffler or other transport equipment using electrical pulses. Electrical pulses are formed between the two ring electrodes (anode and cathode) installed in series along the gas flow. The physical picture of the process is described. A mathematical model has been developed and studied. A deterministic relationship has been established between the engine volume, the number of the crankshaft revolutions, the electric field strength and the charge strength and dynamic viscosity of the gas. Experimental studies have been carried out. The goal of the experiment was to confirm the hypothesis of impact ionization of exhaust gases. The effectiveness of electrical pulse purification has been proven.
Keywords: transport equipment; vehicle; internal combustion engine; muffler; ionization; electrodes; exhaust gas purification